Elaboration of the scale of dispositional greed - Shirko, Svetlana M.; Furmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The article reveals the essence of the concept of greed, its structure and typology. The emphasis is on the content characteristics of dispositional greed. The main attention in this article is focused on the elaboration stages of the Dispositional Greed Scale (DGS). Also are presented the results of evaluating the validity and reliability of the stability and internal consistency of the DGS. Scale elaboration procedure has shown that its indicators are reliability and validity. This toolkit is aimed to studying greed as a stable personal trait.